Efficient neural codes naturally emerge through gradient descent learning - Ari S. Benjamin; Ling-Qi Zhang; Cheng Qiu; Alan A. Stocker; Konrad P. Kording (Nature Communications, 2022)
In animals, sensory systems appear optimized for the statistics of the external world. Here the authors take an artificial psychophysics approach, analysing sensory responses in artificial neural networks, and show why these demonstrate the same phenomenon as natural sensory systems.